Pengaruh Kinerja Gabungan Kelompok Tani Terhadap Keberhasilan Program Usaha Produksi Beras (Studi Pada Gapoktan Dewi Sri Desa Glanggang Kabupaten Malang) - Putri, Anggi Eka Ananda; Yuswita, Effy; Aprilia, Anisa (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
One of the problems that is often experienced by rice farmers is the problem of price fluctuations and selling prices that are below the HPP (Government Purchasing Price). Therefore, to overcome this problem, special efforts are needed to improve the welfare of farmers by involving farmer institutions in the form of farmer group associations (gapoktan). This study aims to analyze the effect of the combined performance of farmer groups seen from individual aspects, leadership, ease of business facilities, and implementation aspects on the success of the rice production business program run by the Dewi Sri Farmer Group Association. This study used a quantitative approach with a total sample of 65 respondents taken purposively. The data analysis method used to determine the effect of farmer group performance on the success of the business program is Structural Equation Modeling – Partial Least Square (SEM-PLS) analysis using WarpPLS Version 7.0 software as an analysis tool. The results showed that the variables of leadership, ease of doing business, and implementation aspects had a positive and significant effect on the success of the rice production business program, while the individual aspect variables had no significant effect.